A ABP como estratégia didática e a astronomia como contexto no ensino da quantidade de movimento - Rodrigues, Magna Coeli Soares (2019)
This work presents a strategy on how to learn the concept of quantity of movement in the context of Astronomy, using as main active methodology the Problem Based Learning (PBL). Through familiar scenarios for the student, Astronomy aroused the curiosity necessary to stimulate the learning about momentum concept and its conservation, giving a new meaning to concepts of mechanics, such as movement and force. This re-signification was made through phenomena related to the Earth and Moon movements, in the solar system, and their influence in our daily life such as Moon phases, eclipses, tidal phenomenon, seasons of the year, microgravity and others. The PBL promoted a proper environment to dialogue, collaboration, cooperation and it stimulated the development of critical thinking in students. In addition to requiring data organization, this methodology encouraged research to satisfy the curiosities raised in the debates, as well as to build the skills needed to solve problems presented to the students. The didactic sequence presented to the classes a video as a previous organizer, followed by two videos tutorials. These were used as instruments to guide how PBL works (steps, role of each participant and the division of the application into tutorials) and how to create conceptual maps, a tool used by the teams to relate the concepts identified in the text. The teams also conducted guided experiments through scripts and videos, they shared ideas during the resolution of didactical physical problems through the TPS (think, pare and share), and participated in a competition with the game Are you a naive star?, elaborated according to the taxonomy of Bloom. Each participant was encouraged to take an active stance in the construction of meanings during the interpretation of the texts, accomplishment of the experiments, the exercises resolution and during the competition in the game. The final product was applied in both the public and private schools by different teachers. Marginal differences were found in the overall results of all schools involved, but the conduction of the practice pointed to an overall evolution in the skills and competences desired. Through the interaction the student had the chance to acquire autonomy, because they have learned to listen, investigate, argue, establish strategies and present a possible solution to the problem.